Post-Harvest Management of Fruits and Vegetables - Janghu, Sandeep; Kumar, Vikas; Yadav, Ashok Kumar (Current Perspectives in Agriculture and Food Science Vol. 7, 2024)
Fruit and vegetable harvest management must be done well in order to maximize quality, reduce post-harvest losses, and increase shelf life. The reasons of post-harvest losses, different post-harvest technologies, and treatments meant to reduce losses and maintain the quality of harvested product. Physiological changes, mechanical damage, incorrect handling and transportation, unfavorable weather conditions, and pest infestations are some of the causes of post-harvest losses. Many post-harvest technologies and treatments have been developed to address these issues. These include the use of technologies to delay senescence and decay, controlled atmosphere storage to control oxygen and carbon dioxide levels, and pre-cooling techniques to lower temperature and slow down physiological processes. Post-harvest procedures including washing, sorting, grading, and waxing also aid in lowering microbial contamination and extending shelf life. Additionally, environmentally friendly ways to maintain freshness while minimizing the impact on the environment are provided by sustainable packaging. Real-time monitoring of the supply chain for environmental conditions and produce quality makes it possible to take prompt action to reduce losses and improve storage conditions.